Online targeting of researchers/academics: Ethical obligations and best practices. Issue 1 (1st February 2019) - Greyson, Devon; Cooke, Nicole; Gibson, Amelia; Julien, Heidi
ABSTRACT: Targeted online harassment of academics has been on the rise in the US and internationally. Such harassment ranges from online threats and hacking to doxxing and organized campaigns to discredit one's work. It has now become an often‐unrecognized part of the job for academics—particularly socially marginalized academics and those who study controversial topics such as race, ethnicity, gender, and sexuality—to work to protect themselves from such attacks. With this increase in intimidation attempts, new questions for the profession arise regarding what skills we should be instilling in trainees, whether professional association and academic units should be taking explicit positions or action on researcher/faculty harassment, and the obligations of our employers with regard to defending faculty, staff, and students. This panel will describe targeted online harassment of academics, discuss models for individual and institutional response, and raise questions for the profession as a whole. Sponsored by SIG ED.